PELATIHAN GURU MATEMATIKA DALAM PENGGUNAAN SOFTWARE GEOGEBRA - Alfi Yunita; Lucky Heriyanti Jufri (Universitas Muhammadiyah Malang, 2020)
Community service aims to train teachers to make learning media using Geogebra. The background of doing this training is the teacher has difficulty to make a representative learning media, so the students have difficulty to understand the subject matter and require a long time to explain the lesson. The method in this community service activity is to provide geogebra training for teachers by demonstration.Then the teachers are given the task to create a media for learning mathematics in polyhedra subject. The results from this activity are the teachers can create interactive and representative mathematics learning media. `